2017
DOI: 10.1080/02713683.2017.1401645
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different amniotic membrane orientations during extraocular muscle surgery in rabbits

Abstract: All AM orientations were equally effective in preventing the development of postoperative adhesions between the extraocular muscle and surrounding tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…The authors concluded that any AMT orientation was effective in preventing adhesions, with no advantage seen in either group. 152 Although there is limited evidence within the literature to support a sutured or sutureless technique, one review article recommends the use of a sutureless technique as it induces less of an inflammatory reaction and results in a shorter operating time. 145 Ocular Surface Wound Healing: Patch Chemical/Thermal Injury Amnion has a range of biological properties that make it attractive for use in the treatment of chemical burns, such as its epitheliotrophic; anti-inflammatory and antineovascular effects.…”
Section: Strabismusmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that any AMT orientation was effective in preventing adhesions, with no advantage seen in either group. 152 Although there is limited evidence within the literature to support a sutured or sutureless technique, one review article recommends the use of a sutureless technique as it induces less of an inflammatory reaction and results in a shorter operating time. 145 Ocular Surface Wound Healing: Patch Chemical/Thermal Injury Amnion has a range of biological properties that make it attractive for use in the treatment of chemical burns, such as its epitheliotrophic; anti-inflammatory and antineovascular effects.…”
Section: Strabismusmentioning
confidence: 99%
“…The authors concluded that any AMT orientation was effective in preventing adhesions, with no advantage seen in either group. 152 Although there is limited evidence within the literature to support a sutured or sutureless technique, one review article recommends the use of a sutureless technique as it induces less of an inflammatory reaction and results in a shorter operating time. 145…”
Section: Strabismusmentioning
confidence: 99%
“…There is a growing body of evidence, evaluating the use of AMs in strabismus surgery. 83 , 84 , 85 , 86 , 87 , 88 , 89 Similar to the present study, a 2019 review article evaluated the use of AMs with different processing methodologies for extraocular muscle surgery. 89 The authors concluded that dried AM does not effectively limit adhesion formation.…”
Section: Discussionmentioning
confidence: 80%
“…78,80,82 There is a growing body of evidence, evaluating the use of AMs in strabismus surgery. [83][84][85][86][87][88][89] Similar to the present study, a 2019 review article evaluated the use of AMs with different processing methodologies for extraocular muscle surgery. 89 The authors concluded that dried AM does not effectively limit adhesion formation.…”
Section: Ddham Supports An Initial Inflammatory Response Followed By ...mentioning
confidence: 93%
“…To isolate the amnion, several pregnant and parturient New Zealand white rabbits were subjected to cesarean section ( Kassem et al, 2018 ). The amniotic membrane was removed under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%